Rapid activation and inactivation of fatty acid synthesis from glucose in vivo - N. Baker (Journal of Lipid Research, 1972)
The flux of glucose carbon to total body fatty acids was measured in unanesthetized mice either after fasting or 50–80 min after they nibbled a small test meal containing 120 mg of glucose (fasted–refed). Flux was calculated from plasma [14C]glucose specific activity curves and from total body 14C-labeled fatty acid 30 min after intravenous injection of tracer [14C]glucose. Mobilization of liver glycogen, changes in the body glucose pool size, and total flux of carbon through the glucose pool during periods of fasting and refeeding were defined. Liver glycogen was almost completely depleted 8 hr after food removal. Body glucose pool size fell during fasting and increased after refeeding the test meal. Irreversible disposal rate of glucose C varied directly with body glucose pool size; but flux of glucose C into fatty acids increased exponentially as body glucose concentration increased. Within an hour after nibbling a small test meal, the flux of glucose C into total body fatty acids increased 700% in mice previously starved for 24 hr. However, flux of glucose C into fatty acids in postabsorptive mice (food removed for 2 hr; livers rich in glycogen) was only about 2% of the value calculated from published studies in which the incorporation of an intubated [14C]glucose load into total body fatty acid was measured in mice. A possible explanation for this phenomenon is presented.